Integrating basic sciences into clerkship rotation utilizing Kern’s six-step model of instructional design: lessons learned - Satwat Hashmi; Qamar Riaz; Husnain Qaiser; Saira Bukhari (BMC Medical Education, 2024)
Abstract Background It is generally agreed that basic and clinical sciences should be integrated throughout the undergraduate medical education, however, there is still need for continued formal integration of basic sciences into clinical clerkship in many medical schools across the globe. Methods Utilizing Kern’s Six-Step Model of Instructional Design, we aimed to develop an intervention that would facilitate cognitive integration of basic and clinical sciences. After problem identification and targeted needs assessment through focused group discussion with the students and faculty, objectives were devised with an implementation plan of using flipped class approach to develop a content-focused and learner-centered teaching strategy. This intervention was piloted in the 2-week cardiology clerkship in Year 5. Evaluation of the content, integration, student and faculty experiences were recorded through in-depth interviews, FGDs and a formative MCQ test. Results Flipped classroom based integrated sessions were successfully developed. The implementation phase was met with challenges that primarily stemmed from the diverse teaching styles among faculty members, hesitance to deviate from conventional practices, variations in clinic timings, and demanding schedules. Noteworthy observations were in terms of ownership of the project, the need for faculty development in modern student-centered teaching pedagogies, opportunities for content improvement, scheduling of sessions, and suggestion of revisiting fundamental concepts in basic sciences through a brief boot camp-style session at the onset of the clerkship. The role of flipped case model and clinical cases in integrating basic sciences into clinical sciences were appreciated by the students. Standardization in teaching practices was identified as the major challenge by the faculty. Conclusions A functional, learner-centered framework of cognitive integration of basic sciences in clinical sciences curriculum of cardiology rotation was developed with a potential to be implemented in other clerkship rotations.